Implementation and evaluation of a standardised performance profile intervention with collegiate athletes. Issue 3 (4th May 2021) - Chow, Graig M.; Castillo, Elmer A.; Luzzeri, Matteo; Bird, Matthew D.
Abstract : Performance profiling is a technique commonly utilised by sport psychology practitioners to assist athletes in identifying and understanding their perceived strengths and weaknesses. Although a number of studies have investigated and described the usefulness of performance profiling, there is limited empirical research using standardised protocols for implementation and pre–post designs. The purpose of this study was to examine the efficacy, validity, and practitioner utility of a revised performance profile intervention [Gucciardi, D. F., & Gordon, S. (2009). Revisiting the performance profile technique: Theoretical underpinnings and application. The Sport Psychologist, 23, 93–117. doi:10.1123/tsp.23.1.93] delivered in a team setting. Specifically, we examined the extent to which the intervention impacted self-awareness, intrinsic motivation, stigma tolerance, and confidence in sport psychology consultation, as well as perceived usefulness and future application of the technique. Participants were 98 (male = 30, female = 68) varsity and club-level collegiate athletes who completed measures of self-awareness, intrinsic motivation, and sport psychology attitudes at pre-intervention and post-intervention, and a post-assessment evaluation. Results revealed that the intervention was efficacious in increasing athletes' confidence in sport psychology consultation and intrinsic motivation from pre-intervention to post-intervention, while self-awareness and stigma tolerance did not significantly improve. Analysis of performance profile worksheets provided evidence for the validity of the technique and its utility for practitioners. Thematic-analysis of post-intervention feedback revealed specific perceived benefits of the technique and future application.